The Roles of Slang Within a Literary Composition. - Mamajanova G‘uncha Xemrayevna; Shakirova Saida Tukhtajonovna (Academia One, 2024)
This article investigates the diverse functions of slang within literary compositions, probing the strategies employed by authors in utilizing slang to delineate characters, set the scene, evoke ambiance, and convey thematic motifs. By undertaking an in-depth analysis of a range of literary works, this research endeavors to unveil the manifold roles that slang assumes within the context of literature
Keywords: anthology; short stories; exhibit